2021
DOI: 10.1177/0194599821989637
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic Extranodal Extension in HPV‐Negative Head and Neck Cancer and the Role of Adjuvant Chemoradiation

Abstract: Objective Pathologic extranodal extension (ENE) is an important adverse feature for human papillomavirus (HPV)–negative head and neck squamous cell carcinoma (HNSCC), but the prognostic significance of microscopic ENE (ENEmi) and role of adjuvant concurrent chemoradiation (CRT) for ENEmi remain unclear. This study evaluates (1) the prognostic significance of ENEmi in HPV-negative HNSCC and (2) whether adjuvant CRT is associated with improved overall survival (OS) for these patients. Study Design Retrospective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
(114 reference statements)
0
4
0
Order By: Relevance
“…Capturing the extent of ENE in N classification is important for two reasons. Several studies have demonstrated the unique prognosis of minor and major ENE subgroups 9–11,22,23 . The stratification of ENE into minor or major may also have therapeutic implications.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Capturing the extent of ENE in N classification is important for two reasons. Several studies have demonstrated the unique prognosis of minor and major ENE subgroups 9–11,22,23 . The stratification of ENE into minor or major may also have therapeutic implications.…”
Section: Discussionmentioning
confidence: 99%
“…The stratification of ENE into minor or major may also have therapeutic implications. Two studies demonstrated that patients with minor ENE may not benefit from adjuvant chemoradiotherapy, unlike those with major ENE 10,11 . The recommendation by the ICCR to capture minor or major ENE as a core element in pathologic reporting of neck dissection specimens will result in additional real‐world data to validate the importance of this pathologic feature.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations